Toward the Development of a Lupus Interactive Navigator to Facilitate Patients and Their Health Care Providers in the Management of Lupus: Results of Web-Based Surveys - Neville, Carolyn (JMIR Res Protoc, 2014)
BACKGROUND: Systemic lupus erythematosus is an inflammatory autoimmune disease associated with high morbidity and unacceptable mortality. Information and management tools are needed to help persons with lupus cope with their illness and facilitate health care providers in the delivery of care. OBJECTIVE: The objective of the study was to assess the needs and find solutions to support persons with lupus and their health care providers. METHODS: Web-based surveys were distributed across Canada to persons with lupus and their relatives (n=3119), rheumatologists (n=517), and arthritis health professionals (AHPs) (n=226) by Lupus Canada, the Canadian Rheumatology Association, and the Arthritis Health Professions Association, respectively. RESULTS: The survey sample comprised 665 (21.3%) persons with lupus, 98 (19.0%) rheumatologists, and 74 (32.7%) AHPs. Among the participants with lupus, 92.4% were female, the average age was 46.8 (SD 12.7) years, 79.2% were Caucasian, and 58.8% were employed. All Canadian provinces and territories were represented. The majority (43.3%) of respondents were from Ontario. Mean disease duration was 10.2 (SD 9.5) years, and 41.9% rated their global assessment as fair or poor. There was high agreement between lupus participants and health care providers regarding disease-specific information topics. All groups rated topics related to lupus, fatigue, medications, and stress as most important. Ratings differed among lupus participants and their health care providers regarding perceived helpfulness of some of the patient tools, such as the option to view test results. Needs differed for persons with lupus based on age, sex, depression, stress, and disease activity. Differences in health care provider needs were based on amount of experience in treating lupus. CONCLUSIONS: Information and support tools needed for persons with lupus and their health care providers were identified. These results will help guide us in the development of a Web-based Lupus Interactive Navigator as an intervention tool to help persons with lupus self-manage their disease and to facilitate heath care providers in clinical management.